Modeling and Analysis of the Effect of Holes in Reinforced Concrete Column Structures - Yohanes Laka Suku; Kristoforus Je (Journal of the Civil Engineering Forum, 2020)
Holes are often made inside the column structure for plumbing, mechanical, and electrical installation purposes may affect the structural performance of the column. Therefore, this paper aims to model and analyze the effect of holes in reinforced concrete column structures due to lateral loads. Data were obtained from the reference frame structure of the previous researcher, with varying centric column holes of 0%, 2%, 4%, 6%, 8%, 10%, and 12%, respectively to the column cross-sectional area. Furthermore, a hole with a ratio of 4% to the column cross-sectional area was placed at 5 and 10 mm eccentric to the center of column cross-section to examine the influence of holes position in the perforated column. The frame structure was modelled and analyzed by Finite Element (FE) using ABAQUS software. The result showed that the maximum load, displacement, and crack pattern resulted from the model is close to the experimental result. The results of the analysis showed that with the hole size of 2% to 12% of the column cross-sectional area, the frame strength was reduced by 5.43% to 15.56%.  The frame strength was also reduced by 2.77% and 6.14% when the hole placed 5mm and 10 mm eccentric to the center of the column cross-section area. The displacement of the frame also decreases by 59.63% to 74.60% when the holes with the ratio of 2% to 12% to the column cross-sectional area exist in the column. The existence of eccentric holes on the column reduced the performance of the frame structure, by decreasing its strength, displacement and ductility.